Symptom clusters on primary care medical service trips in five regions in Latin America - Christopher Dainton; Charlene Chu (Springer, 2019)
Short-term primary care medical service trips organized by the North American non-governmental organizations (NGOs) serve many communities in Latin America that are poorly served by the national health system. This descriptive study contributes to the understanding of the epidemiology of patients seen on such low-resource trips. An analysis was conducted on epidemiologic data collected from anonymized electronic medical records on patients seen during 34 short-term medical service trips in five regions in Ecuador, Guatemala, and the Dominican Republic between April 2013 and April 2014. A total of 22,977 patients were assessed by North American clinicians (physicians, nurse practitioners, physician assistants) on primary care, low-resource medical service trips. The majority of patients were female (67.1%), and their average age was 36. The most common presenting symptoms in all regions were general pain, upper respiratory tract symptoms, skin disorders, eye irritation, dyspepsia, and nonspecific abdominal complaints; 71-78% of primary care complaints were easily aggregated into well-defined symptom clusters. The results suggest that guideline development for clinicians involved in these types of medical service trips should focus on management of the high-yield symptom clusters described by these data.